Development of online appointment system using forward chaining algorithm for Student and lecturer in FTMSK / Sharizal Sharif - Sharif, Sharizal (Faculty of Computer and Mathematical Sciences, 2007)
Appointment System is one of system that manages time by performing scheduling process. This research paper was conducted to develop an online appointment system for student and lecturer in Faculty of Information Technology (FTMSK), UiTM Shah Alam. Methodology approach used for progression phase is SDLC method and used Decision Support System model to design and develop the system prototype. This research more focuses on the designing system engines using Forward Chaining algorithm. The final part of the research produce a prototype of appointment system and the researcher did analysis to the system for documentation.